Characterization of biochars of different origin and application to the anaerobic digestion of source-selected organic fraction of municipal solid waste under batch conditions and at different dosages - García-Prats, Marta; González, Daniel; Sánchez, Antoni (Frontiers in Chemical Engineering, 2024)
Anaerobic digestion (AD) is a wide-spread strategy to manage organic waste and recover valuable products but faces some limitations that could be overcome with additives like biochar (BC). The production of BC defines its properties, which in turn determine its effect on AD performance and methane yield. In this study, three biochars (BC1, BC2 and BC3) were characterized using several techniques (SEM imaging, BET, GC, ICP and FTIR). The properties of BC were found to be defined both by the feedstock and the production process. The BC were then applied to the AD of the organic fraction of municipal solid waste (OFMSW) using three doses (1, 5 and 10% w/w TS). Compared to the control, there was an increase in methane production in BC3 at doses 1 and 5% (+15 and +30%, respectively) and a decrease in BC1 and BC2 at 1% (-33 and -19%, respectively). The decrease in biogas production was often paired with an increased methane content. A two-way ANOVA analysis showed that the interaction of biochar dose and type had a significant effect on methane yield, meaning that the effect of BC on AD cannot be predicted with the dose or the type alone. When a second substrate feeding was performed, no significant differences on methane production were observed among the experimental conditions. Key aspects to properly assess the economic viability of the process have been also discussed. Further experiments could help to fill knowledge gaps and clarify the roles of BC characteristics and dose on AD performance.